Gerak Dasar sebagai Fondasi: Peran Fundamental Movement Skills dalam Pembentukan Motorik Anak Sekolah Dasar Usia 6 – 9 Tahun - Feldasha Atha Cahya Dewi; Tias Budi Saputri; Kunjung Ashadi (Mutiara Pendidikan dan Olahraga, 2025)
The rapid growth of the digital era significantly reduces children's physical activity, thus having an impact on decreasing gross and fine motor development in elementary school-age children. The habit of excessive use of gadgets causes children to tend to be passive and less involved in structured movement activities. Fundamental Movement Skills (FMS), as the basis of motor competence which includes locomotor, non-locomotor, and manipulative skills, shows increasingly less than optimal development in early childhood and school age. This study examines the contribution of FMS to children's motor development and evaluates the effectiveness of FMS-based learning media, especially modified snake and ladder games, in improving students' basic movement skills. The study used a descriptive-correlational quantitative design involving 40 students aged 6–9 years who were selected through purposive sampling techniques. Data collection was carried out using the Test of Gross Motor Development-2 (TGMD-2) instrument, structured observation rubrics, and supporting documentation. Data analysis used descriptive statistics and Pearson correlation tests to see the relationships between variables. The findings of this research are expected to be the basis for the development of more innovative, adaptive, and fun physical education programs to support children's motor development in the midst of the challenges of the digital era.